Conversion liquid, surface treatment method, electronic equipment and preparation method
By using a conversion liquid containing components such as organosiloxane, fluorosilate, and a treatment liquid with colored ions, the surface treatment liquid of magnesium alloy workpiece is surface treated to form a transparent color conversion film, which solves the problems of gloss and color diversification of the surface of magnesium alloy workpieces in the prior art, and a film layer with high transparency and corrosion resistance is achieved.
Patent Information
- Application Number
- CN202510230785.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-27
- Publication Date
- 2025-06-10
AI Technical Summary
In the prior art, when converting the surface of magnesium alloy workpieces, it is difficult to maintain the metallic gloss, and it is impossible to effectively achieve color diversification.
A conversion liquid containing organosiloxane, fluorosilicate, silica sol, ammonium metavanadate and solvent is used to surface treatment on the surface of the magnesium alloy workpiece to form a transparent oxide film, and a treatment liquid with colored ions reacts with oxidizing substances adsorbed on the surface of the film to form a colored conversion film.
While maintaining the metallic gloss of magnesium alloy workpieces, a transparent film layer with a specified color is formed, which improves the corrosion resistance and bonding of the film layer, and meets the diversity of the appearance of electronic products.
Smart Images

Figure CN120119236A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of surface treatment, and in particular to a conversion solution, a surface treatment method, an electronic device and a preparation method thereof. Background Art
[0002] With the improvement of consumers' living standards, consumers' requirements for products (such as electronic products like mobile phones and laptops) are getting higher and higher. They not only pay attention to the quality of products, but also focus on the texture and beauty of the product appearance. Color matching is an important means to achieve product differentiation.
[0003] In the related art, to meet consumers' needs for diverse product appearances, different color requirements are achieved by performing process treatments on the product surface. The conversion treatment process usually uses high-concentration acidic solutions such as iron salts and manganese salts to form an insoluble and infusible oxide film with color on the product surface. However, the metallic luster after the conversion treatment is poor. Summary of the Invention
[0004] Based on the problems existing in the related art, embodiments of this application provide a conversion solution, a surface treatment method, an electronic device and a preparation method thereof.
[0005] The technical solution of the embodiments of this application is implemented as follows:
[0006] In a first aspect, embodiments of this application provide a conversion solution for surface treatment, and the conversion solution at least includes organosiloxane, fluorosilicate, silica sol, ammonium metavanadate and a solvent.
[0007] In some embodiments, the conversion solution is used for surface treatment of metal structures.
[0008] In some embodiments, the content of the organosiloxane in the conversion solution is 18 - 32 g / L;
[0009] The content of the fluorosilicate in the conversion solution is 8 - 10 g / L;
[0010] The content of the silica sol in the conversion solution is 10 - 12 g / L;
[0011] The content of the ammonium metavanadate in the conversion solution is 1 - 3 g / L.
[0012] In some embodiments, the organosiloxane includes γ-(2,3-epoxypropoxy)propyltrimethoxysilane; the fluorosilicate includes potassium fluorosilicate; the solvent includes deionized water;
[0013] The conversion liquid further includes ammonium bifluoride, sodium citrate, fatty alcohol polyoxyethylene ether, an acidic regulator and a basic regulator. The acidic regulator includes citric acid or hydrofluoric acid, and the basic regulator includes ammonia water or sodium hydroxide; the pH value of the conversion liquid is between 6.0 and 6.5.
[0014] In some embodiments, the content of ammonium bifluoride in the conversion liquid is 8-10 g / L;
[0015] The content of sodium citrate in the conversion liquid is 5-8 g / L;
[0016] The content of fatty alcohol polyoxyethylene ether in the conversion liquid is 0.25-0.4 g / L.
[0017] In a second aspect, an embodiment of the present application provides a surface treatment method, which includes:
[0018] Using a conversion liquid to perform surface treatment on the surface of a magnesium alloy workpiece, and forming a conversion film with an oxidizing substance adsorbed on the surface of the magnesium alloy workpiece; wherein, the pH value of the conversion liquid is between 6.0 and 6.5;
[0019] Based on a treatment liquid having a colored ion, reacting with the oxidizing substance adsorbed on the surface of the conversion film to form a colored conversion film on the surface of the conversion film.
[0020] In some embodiments, the step of using a conversion liquid to perform surface treatment on the surface of a magnesium alloy workpiece and forming a conversion film with an oxidizing substance adsorbed on the surface of the magnesium alloy workpiece includes:
[0021] Under the first process conditions, using the conversion liquid to soak or spray the magnesium alloy workpiece to form the conversion film with the oxidizing substance adsorbed on the surface of the magnesium alloy workpiece;
[0022] Wherein, the transparency of the conversion film is greater than a preset transparency threshold.
[0023] In some embodiments, the conversion liquid at least includes organosiloxane, fluorosilicate, silica sol, ammonium metavanadate and a solvent;
[0024] The step of using the conversion liquid to soak or spray the magnesium alloy workpiece to form the conversion film with the oxidizing substance adsorbed on the surface of the magnesium alloy workpiece includes:
[0025] Based on the organosiloxane, fluorosilicate, silica sol and ammonium metavanadate in the conversion liquid, chemically reacting with the magnesium alloy workpiece to generate a conversion film with metavanadate adsorbed on the surface of the magnesium alloy workpiece;
[0026] Among them, the difference between the refractive index of the magnesium alloy workpiece with the conversion film and the refractive index of the magnesium alloy workpiece is less than a preset threshold, and the conversion film is a protective film composed of a composite of magnesium oxide and silicon oxide.
[0027] In some embodiments, the treatment liquid based on a colored ion reacts with the oxidizing substance adsorbed on the surface of the conversion film to form a colored conversion film on the surface of the conversion film, including:
[0028] Under the second process conditions, the magnesium alloy workpiece with the conversion film adsorbed with the oxidizing substance on the surface is soaked or sprayed with the treatment liquid, so that the colored ions in the treatment liquid react with the oxidizing substance to form the colored conversion film on the surface of the conversion film;
[0029] Among them, the pH value of the treatment liquid is greater than the pH value of the conversion liquid, and the treatment liquid includes: a catalyst, a complexing agent, a colored ion compound, sodium gluconate, sodium citrate, and a solvent;
[0030] The solvent includes deionized water; the complexing agent includes disodium ethylenediaminetetraacetate; the catalyst includes one of the following: potassium fluozirconate and manganese sulfate; the colored ion compound includes at least one of the following: iron ion complex, copper ion complex, manganese ion complex, and nickel ion complex.
[0031] In a third aspect, an embodiment of the present application provides a magnesium alloy workpiece, and a colored conversion film is formed on the surface of the magnesium alloy workpiece;
[0032] The colored conversion film is formed by using a conversion liquid to perform surface treatment on the surface of the magnesium alloy workpiece to form a conversion film with an oxidizing substance adsorbed on the surface of the magnesium alloy workpiece; based on a treatment liquid with a colored ion, reacting with the oxidizing substance adsorbed on the surface of the conversion film to form on the surface of the conversion film; among them, the pH value of the conversion liquid is between 6.0 and 6.5.
[0033] In a fourth aspect, an embodiment of the present application provides an electronic device, and the electronic device includes a magnesium alloy workpiece, and a colored conversion film is formed on the surface of the magnesium alloy workpiece;
[0034] The colored conversion film is formed by using a conversion liquid to perform surface treatment on the surface of the magnesium alloy workpiece to form a conversion film with an oxidizing substance adsorbed on the surface of the magnesium alloy workpiece; based on a treatment liquid with a colored ion, reacting with the oxidizing substance adsorbed on the surface of the conversion film to form on the surface of the conversion film; among them, the pH value of the conversion liquid is between 6.0 and 6.5.
[0035] In a fifth aspect, an embodiment of the present application provides a preparation method, and the preparation method includes:
[0036] Obtain a die-cast magnesium alloy workpiece;
[0037] Perform surface treatment on a preset position of the magnesium alloy workpiece to form a colored conversion film on the surface of the preset position;
[0038] Wherein, the surface treatment includes using a conversion solution to perform surface treatment on the surface of the magnesium alloy workpiece to form a conversion film with an oxidizing substance adsorbed on the surface of the magnesium alloy workpiece; based on a treatment solution with colored ions, reacting with the oxidizing substance adsorbed on the surface of the conversion film to form a colored conversion film on the surface of the conversion film; wherein, the pH value of the conversion solution is between 6.0 and 6.5. Description of the Drawings
[0039] Figure 1 It is a schematic diagram of a magnesium alloy workpiece in the related art provided by an embodiment of the present application;
[0040] Figure 2 It is a schematic diagram of the surface of a magnesium alloy workpiece with a conversion film provided by an embodiment of the present application;
[0041] Figure 3 It is an optional flowchart of a surface treatment method provided by an embodiment of the present application;
[0042] Figure 4 It is a schematic diagram of a magnesium alloy workpiece with a light blue film layer provided by an embodiment of the present application;
[0043] Figure 5 It is a schematic diagram of a magnesium alloy workpiece with a light yellow film layer provided by an embodiment of the present application;
[0044] Figure 6 It is a schematic diagram of the structure of a die-cast magnesium alloy workpiece provided by an embodiment of the present application;
[0045] Figure 7 It is a flowchart of forming a colored film on the surface of a magnesium alloy provided by an embodiment of the present application. Detailed Embodiments
[0046] Hereinafter, embodiments of the conversion solution, the surface treatment method, the electronic device, and the preparation method provided by the present application are specifically disclosed with appropriate reference to the drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually identical structures are omitted. This is to avoid the following description from becoming unnecessarily long and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter recited in the claims.
[0047] The "ranges" disclosed in this application are defined in the form of a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of a particular range. The ranges defined in this way can include or exclude the end values, and can be combined arbitrarily, that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60 - 120 and 80 - 110 are listed for a specific parameter, ranges of 60 - 110 and 80 - 120 are also contemplated. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4, and 5 are listed, then the following ranges are all contemplated: 1 - 3, 1 - 4, 1 - 5, 2 - 3, 2 - 4, and 2 - 5. In this application, unless otherwise specified, the numerical range "a - b" represents an abbreviated representation of any combination of real numbers between a and b, where a and b are both real numbers. For example, the numerical range "0 - 5" means that all real numbers between "0 - 5" are fully listed herein, and "0 - 5" is only an abbreviated representation of these numerical combinations. Additionally, when stating that a certain parameter is an integer ≥2, it is equivalent to disclosing that the parameter is, for example, the integers 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0048] If there is no special instruction, all embodiments and optional embodiments of this application can be combined with each other to form new technical solutions.
[0049] If there is no special instruction, all technical features and optional technical features of this application can be combined with each other to form new technical solutions.
[0050] If there is no special instruction, all steps of this application can be carried out sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method can include steps (a) and (b) carried out sequentially, or can also include steps (b) and (a) carried out sequentially. For example, when it is mentioned that the method may further include step (c), it means that step (c) can be added to the method in any order. For example, the method can include steps (a), (b), and (c), or can also include steps (a), (c), and (b), or can also include steps (c), (a), and (b), etc.
[0051] If there is no special instruction, the terms used in this application have the well-known meanings commonly understood by those skilled in the art. If there is no special instruction, the numerical values of the various parameters mentioned in this application can be measured by various commonly used testing methods in the art. For example, they can be measured according to the testing methods given in this application.
[0052] In related technologies, to achieve the color matching of the overall design of electronic products and better composite with the coating layer to obtain an ideal color, it is necessary to perform a color high-permeability conversion film treatment on the surface of the substrate, so as to achieve consistency with the main color.
[0053] The inventors of the present application found that in the conversion treatment process of related technologies, to achieve the color of the surface film layer of the electronic product housing (usually made of magnesium alloy material), an opaque oxide film layer with a certain thickness composed of metal oxides such as magnesium (Mg), aluminum (Al), and iron (Fe) is formed by chemical means. To implement this process, related technologies often use solutions with relatively high acidity or strong alkalinity for chemical reactions. However, these solution environments cause relatively large damage to the high-brightness surface of the magnesium alloy, resulting in the oxidation and dissolution of the high-brightness surface, forming a mixed film layer of an oxide film and a precipitation film. The thickness of the film is relatively thick, which will cause the magnesium alloy workpiece to lose the original metallic luster of the metal. As Figure 1 shown, Figure 1 FIG. 1 is a schematic diagram of a magnesium alloy workpiece in related technologies provided by an embodiment of the present application. The magnesium alloy workpiece 101 reacts with a permanganate-phosphate solution to generate a passivation film on the surface of the workpiece. This film can protect the surface of the magnesium alloy, but due to the excessive corrosion of the acidic solution, the surface luster of the magnesium alloy cannot be maintained.
[0054] In order to maintain the luster of the high-brightness metal on the surface of the electronic product, meet the color requirements, and at the same time achieve good corrosion resistance and adhesion of the overall coating, there is an urgent need for a new surface treatment method to treat the magnesium alloy workpiece, so that the treated magnesium alloy workpiece can maintain the original high-brightness luster, and can be colored according to requirements and is corrosion-resistant.
[0055] In the embodiment of the present application, to form a transparent film layer with a specified color and corrosion resistance on the surface of the metal housing of the electronic product, a solution combining silane and fluorosilicate is used to perform surface treatment on the metal housing of the electronic product (for example, it can be a magnesium alloy workpiece) to form a transparent film. In this way, the impact on the surface of the magnesium alloy workpiece is small, and the high-brightness surface of the magnesium alloy workpiece will not be oxidized and dissolved. Then, through the reaction of the oxidizing substance adsorbed on the surface after the formation of the transparent film with the colored ions, a colored film is formed, and finally a conversion film layer with a specified color is formed on the surface of the magnesium alloy workpiece, which can not only resist corrosion, but also provide good adhesion and weather resistance for subsequent painting.
[0056] Based on this, in the embodiment of the present application, a conversion liquid can be used to first perform surface treatment on the surface of the magnesium alloy workpiece to form a conversion film with an oxidizing substance adsorbed on the surface of the magnesium alloy workpiece, and then a treatment liquid with colored ions is used to react with the oxidizing substance adsorbed on the surface of the conversion film to form a colored conversion film on the surface of the conversion film.
[0057] In some embodiments, the conversion solution may at least include organosiloxane, fluorosilicate, silica sol, ammonium metavanadate, and a solvent. Here, the fluorosilicate, silica sol, and organosiloxane react with the surface layer of the magnesium alloy to form a nano-transparent film composed of magnesium oxide and silicon oxide.
[0058] In some embodiments, the silica sol may be a colloidal solution composed of nano-scale silicon dioxide particles. During the reaction, the silica sol and organosiloxane react with the oxides or hydroxyl groups on the surface of the magnesium alloy, and through hydrolysis and condensation reactions, a uniform film composed of silicon dioxide (SiO 2 ) and magnesium oxide is formed. At the same time, there are a large number of silanol groups (Si-OH) on the surface of the silica sol and organosiloxane, which have high reactivity and can bond with the hydroxyl groups on the surface of the magnesium alloy workpiece, thereby improving the adhesion of the conversion film to the substrate.
[0059] Here, 30% silica sol can be used, that is, the content of silicon dioxide in the silica sol accounts for 30%, and the rest is water or other solvents.
[0060] In some embodiments, the fluorosilicate can be used to provide fluoride ions and silicate ions during the reaction. The silicate ions can react with the magnesium ions on the surface of the magnesium alloy to form silicon oxide, and the fluoride ions can react with the oxides (such as MgO) on the surface of the magnesium alloy to promote the formation of the oxide film. The fluoride ions can improve the density and hardness of the film layer, thereby enhancing the corrosion resistance of the film layer.
[0061] In some embodiments, the surface of the magnesium alloy workpiece will be hydroxylated, that is, a layer of magnesium-rich oxides (such as magnesium oxide) and hydroxides (such as Mg(OH) 2 ) will be formed on the surface. These hydroxides provide a large number of hydroxyl groups (-OH). After the organosiloxane is hydrolyzed, silanol groups (i.e., silanol groups Si-OH) are formed. The silanol groups chemically react with the hydroxyl groups on the surface of the magnesium alloy workpiece to generate siloxymagnesium bonds (Si-O-Mg), thereby firmly binding the formed transparent film to the surface of the magnesium alloy, enhancing the binding force between the transparent film and the magnesium alloy workpiece, and also improving the flexibility and corrosion resistance of the film layer through an organic-inorganic hybrid structure.
[0062] In some embodiments, ammonium metavanadate can be used to provide metavanadate (VO 3 2- ). The metavanadate can adsorb on the surface of the conversion film already formed on the surface of the magnesium alloy. The metavanadate ions can react with the treatment solution containing colored ions to form a compound with a specific color attached to the surface of the conversion film, which can not only endow the film layer with a specific color, but also enhance the chemical stability and corrosion resistance of the film layer.
[0063] In some embodiments, ammonium metavanadate in the conversion solution can be replaced with other compounds that can provide acid radicals and the acid radicals can be adsorbed on the surface of the conversion film. For example, molybdates (such as ammonium molybdate or sodium molybdate) or chromates (such as potassium chromate or sodium chromate).
[0064] In some embodiments, the film layer of the conversion film can be composed of nanoscale MgO and SiO 2 particles. The thickness of the conversion film can be nanoscale (the thickness can be between 200 and 500 nanometers). Due to the size effect of the nanoparticles, and the good transparency of magnesium oxide and silicon oxide in the visible light range, and only a small amount of magnesium dissolves under weak acid, the conversion film has high transparency. Here, the transparency can be greater than the transparency threshold (which can be 85%), and the transparency threshold can be used to characterize the light transmittance of the conversion film, so that the magnesium alloy workpiece with the conversion film can maintain the metallic luster of the magnesium alloy material.
[0065] In the embodiments of the present application, by reacting fluorosilicate, silica sol, organosiloxane and ammonium metavanadate with the surface layer of the magnesium alloy workpiece, a conversion film including at least magnesium oxide and silicon oxide is formed. It can not only maintain the metallic effect of the magnesium alloy workpiece, but also make the surface of the magnesium alloy workpiece have a nanoscale film layer with a certain thickness to achieve the adhesion between the magnesium alloy workpiece and the subsequent coating, providing good adhesion and weather resistance for the subsequent coating; at the same time, ammonium metavanadate makes the surface of the conversion film adsorb metavanadate ions, which can react with the treatment solution with colored ions to form a conversion film with a specific color, so as to enhance the diversity of the appearance of electronic products.
[0066] In some embodiments, the conversion solution can be used for the surface treatment of metal structures. The embodiments of the present application give an example that the metal structure is a magnesium alloy workpiece, but the metal structure is not limited to the magnesium alloy workpiece provided in the embodiments of the present application, and can also be other metal structures that need to form a colored film.
[0067] Figure 2 is a schematic diagram of the surface of the magnesium alloy workpiece with a conversion film provided by the embodiments of the present application. As Figure 2 shown, the magnesium alloy workpiece 201 can be used as the side wall of the housing of an electronic device. By reacting the conversion solution provided by the embodiments of the present application with the magnesium alloy workpiece, a conversion film that can maintain the metallic luster effect of the magnesium alloy workpiece is obtained.
[0068] In some embodiments, the content of organosiloxane in the conversion solution can be 18-32 g / L to provide a sufficient amount of silicon-oxygen-magnesium bonds (Si-O-Mg) to firmly bind the formed transparent film to the magnesium alloy surface. Exemplarily, the content of organosiloxane in the conversion solution can be 18, 20, 25, 30 or any value within the range composed of any two of them.
[0069] In some embodiments, the content of fluorosilicate in the conversion solution can be 8-10 g / L. Exemplarily, the content of fluorosilicate in the conversion solution can be 8, 9, 10 or any value within the range composed of any two of these values.
[0070] In some embodiments, the content of silica sol in the conversion solution can be 10-12 g / L. Exemplarily, the content of silica sol in the conversion solution can be 10, 11, 12 or any value within the range composed of any two of these values.
[0071] In some embodiments, the content of ammonium metavanadate in the conversion solution can be 1-3 g / L. Exemplarily, the content of ammonium metavanadate in the conversion solution can be 1, 2, 3 or any value within the range composed of any two of these values.
[0072] In the embodiments of the present application, fluorosilicate, silica sol, organosiloxane and ammonium metavanadate can act synergistically within the above content ranges to form a conversion film with good transparency and corrosion resistance, and oxidizing substances such as metavanadate ions are adsorbed on the film surface.
[0073] In some embodiments, the organosiloxane can be γ-(2,3-epoxypropoxy)propyltrimethoxysilane (KH-560), and can also be any feasible organosiloxane that can provide silanol groups after hydrolysis, such as γ-aminopropyltriethoxysilane (KH-550), γ-methacryloxypropyltrimethoxysilane (KH-570) and N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane (KH-792). The specific type of organosiloxane is not limited in the embodiments of the present application.
[0074] In some embodiments, the fluorosilicate can be potassium fluorosilicate, and can also be any feasible fluorosilicate that can provide fluoride ions, such as potassium fluorosilicate and magnesium fluorosilicate. The specific type of fluorosilicate is not limited in the embodiments of the present application.
[0075] In some embodiments, in addition to the components in the foregoing embodiments, the conversion solution can further include ammonium bifluoride, sodium citrate, fatty alcohol polyoxyethylene ether, acid regulator and base regulator.
[0076] Here, ammonium bifluoride can provide hydrofluoric acid (HF) to form an acidic environment in the conversion solution, promote micro-etching on the surface of the magnesium alloy, and enhance the adhesion of the conversion film. At the same time, HF can react with the silicon-oxygen bond in the silica sol or fluorosilicate to form a denser silicon-oxygen network structure, thereby improving the corrosion resistance and transparency of the conversion film.
[0077] In some embodiments, sodium citrate can provide citrate ions, which can form complexes with magnesium ions, thereby inhibiting over-corrosion on the surface of magnesium alloy workpieces, promoting the formation of a uniform conversion film at the same time, and improving the quality and uniformity of the conversion film.
[0078] In some embodiments, fatty alcohol polyoxyethylene ether (AEO) is an active agent, which can promote the formation of a more uniform conversion film. At the same time, AEO can also reduce the formation of bubbles during the formation of the conversion film, avoid the generation of film layer defects, and further improve the quality of the conversion film.
[0079] In some embodiments, the conversion solution may further include an acidic regulator and a basic regulator for adjusting the pH value of the conversion solution. The acidic regulator can be citric acid or hydrofluoric acid, and the basic regulator can be ammonia water or sodium hydroxide. By adjusting the contents of the acidic regulator and the basic regulator, the pH value of the conversion solution is made to be between 6.0 and 6.5. Therefore, the contents of the acidic regulator and the basic regulator are set according to requirements, and no specific numerical values are set in the embodiments of the present application. The conversion solution of weak acid will not cause excessive dissolution on the surface of magnesium alloy workpieces and keeps the metallic luster of magnesium alloy workpieces.
[0080] In some embodiments, the content of ammonium bifluoride in the conversion solution can be 8 - 10 g / L. Exemplarily, the content of ammonium bifluoride in the conversion solution can be 8, 9, 10, or a value within the range composed of any two of them.
[0081] In some embodiments, the content of sodium citrate in the conversion solution can be 5 - 8 g / L. Exemplarily, the content of sodium citrate in the conversion solution can be 5, 7, 8, or a value within the range composed of any two of them.
[0082] In some embodiments, the content of fatty alcohol polyoxyethylene ether in the conversion solution can be 0.25 - 0.4 g / L. Exemplarily, the content of fatty alcohol polyoxyethylene ether in the conversion solution can be 0.25, 0.3, 0.4, or a value within the range composed of any two of them.
[0083] The embodiments of the present application can form a more stable and uniform conversion film through the above components and corresponding contents.
[0084] In some embodiments, based on the foregoing conversion solution, the embodiments of the present application provide a surface treatment method for surface treatment of magnesium alloy based on this conversion solution. Figure 3 is an optional process schematic diagram of the surface treatment method provided by the embodiments of the present application. As Figure 3 shown, the surface treatment method includes step S301 and step S302:
[0085] Step S301: Use a conversion solution to perform surface treatment on the surface of the magnesium alloy workpiece, and form a conversion film with oxidizing substances adsorbed on the surface of the magnesium alloy workpiece; wherein, the pH value of the conversion solution is between 6.0 and 6.5.
[0086] In some embodiments, the magnesium alloy workpiece for surface treatment can be a workpiece after pre - polishing treatment, with a metallic luster and a mirror effect on the surface. To solve the corrosion damage caused by strong acidic solutions to the surface of the magnesium alloy workpiece, the embodiments of the present application use a conversion solution with a pH value between 6.0 and 6.5 to perform surface treatment on the surface of the magnesium alloy workpiece, so as to reduce over - corrosion of the surface of the magnesium alloy workpiece during surface treatment and reduce the damage to the surface gloss and mirror effect of the magnesium alloy workpiece.
[0087] In some embodiments, using a conversion solution to perform surface treatment on the surface of the magnesium alloy workpiece may refer to immersing the magnesium alloy in the conversion solution and uniformly swinging or agitating with air at 20 - 30 °C for 60 - 180 s to form a conversion film with oxidizing substances adsorbed on the surface of the magnesium alloy workpiece.
[0088] Here, the conversion solution can at least include organosiloxane, fluorosilicate, silica sol, ammonium metavanadate, and a solvent. The components in the conversion solution synergistically act to form at least a conversion film including magnesium oxide and silicon oxide, and vanadate ions are adsorbed on the surface of the conversion film. The functions of the components in the conversion solution have been described in the foregoing embodiments and will not be elaborated in this embodiment.
[0089] Step S302: Based on a treatment solution with colored ions, react with the oxidizing substances adsorbed on the surface of the conversion film to form a colored conversion film on the surface of the conversion film.
[0090] In the embodiments of the present application, colored ions refer to ions that exhibit a specific color in an aqueous solution, such as copper ions showing blue, ferrous ions showing light green, ferric ions showing yellow, manganese ions showing pink, etc.
[0091] Here, reacting the treatment solution with the oxidizing substances adsorbed on the surface of the conversion film can be achieved by immersing the magnesium alloy workpiece with the conversion film in the treatment solution and uniformly swinging or agitating with air at 20 - 30 °C for 90 - 180 s, so that the colored ions in the treatment solution react with the oxidizing substances to form a colored conversion film composed of colored oxides, and finally form a highly transparent conversion film layer with color on the surface of the magnesium alloy workpiece.
[0092] In some embodiments, the oxidizing substance can be vanadate ions, and the vanadate ions react with the colored ions to generate a colored conversion film on the surface of the conversion film.
[0093] In the embodiments of the present application, the colored conversion film may be a film layer covering the conversion film.
[0094] In the embodiments of the present application, a conversion film adsorbed with an oxidizing substance is formed by the reaction of the conversion liquid with the surface layer of the magnesium alloy workpiece. This conversion film can not only maintain the metallic effect of the magnesium alloy workpiece, but also enable a nano-film layer with a certain thickness to be formed on the surface of the magnesium alloy workpiece, so as to achieve the adhesion between the magnesium alloy workpiece and the subsequent coating, and provide good bonding force and weather resistance for the subsequent coating. At the same time, the oxidizing substance can react with the treatment liquid containing colored ions to form a conversion film with a specific color, which can enhance the diversity of the appearance of electronic products on the premise of achieving anti-corrosion protection.
[0095] Here, in the embodiments of the present application, a rubber friction resistance test is carried out after the colored film is formed on the surface of the magnesium alloy workpiece. After 1000 times of friction, the base material is not exposed; a peeling test is carried out on the colored film on the surface of the magnesium alloy. After the colored film is scratched, the colored film Peer off < 5% (that is, the peeling ratio of the colored film at the scratched part is less than 5%), thereby proving the adhesion of the colored film; the magnesium alloy workpiece with the scratched colored film is immersed in plasma water at 50 °C for 12 hours, and there is no abnormal change on the surface (that is, no defects such as dents, bubbles, cracks, peeling, rupture, shedding, and exposure of the base material), and the colored film Peer off < 5%; the magnesium alloy workpiece with the scratched colored film is placed in a salt spray test chamber at 35 °C, and a 5% sodium halide solution is sprayed on the position where the colored film is damaged. After 48 hours, it is rinsed with water and placed in an environment below room temperature for 2 hours, and the salt spray test passes; a sweat resistance (acid and alkali) test is carried out on the colored film of the magnesium alloy workpiece, that is, the surface of the magnesium alloy is wiped with a gauze with an acidic or alkaline solution. After 1000 times, there is no obvious color change on the gauze; a thermal cycling test is carried out on the magnesium alloy workpiece with the scratched colored film, and the adhesion, color, and gloss of the colored film do not degenerate; a cleaning agent resistance test is carried out on the colored film of the magnesium alloy workpiece. The magnesium alloy workpiece with the colored film is immersed in a 5% neutral washing solvent for 24 hours, and there is no abnormality; an edge wear resistance test is carried out on the colored film of the magnesium alloy workpiece. After 40 - 80 times of friction, the magnesium alloy workpiece will not be exposed.
[0096] In some embodiments, step S301 can be implemented by step S3011:
[0097] Step S3011: Under the first process conditions, use the conversion liquid to soak or spray the magnesium alloy workpiece to form a conversion film with an oxidizing substance adsorbed on the surface of the magnesium alloy workpiece.
[0098] In the embodiments of the present application, the first process condition may be to soak or spray the magnesium alloy workpiece with a conversion solution at 20 to 30 °C for 90 to 180 s. Here, soaking may be immersing the magnesium alloy workpiece in the conversion solution and performing uniform swinging or air agitation to allow the magnesium alloy workpiece to fully contact the conversion solution and form a uniform conversion film; spraying may be uniformly spraying the conversion solution on the surface of the magnesium alloy workpiece through a spraying system to form a conversion film.
[0099] In some embodiments, the thickness of the conversion film can also be controlled by controlling parameters such as the flow rate and pressure of the spray.
[0100] In the embodiments of the present application, during the soaking or spraying process, acid radicals (such as metavanadate) in the conversion solution will adsorb on the surface of the magnesium alloy workpiece and subsequently react with colored ions to form a colored conversion film.
[0101] In some embodiments, the conversion film has high transparency, and the transparency is greater than a transparency threshold value (which can be 85%), and the transparency threshold value can be used to characterize the light transmittance of the conversion film so that the magnesium alloy workpiece with the conversion film can maintain the metallic luster of the magnesium alloy material.
[0102] In the embodiments of the present application, the conversion film has good transparency, does not affect the optical properties of the magnesium alloy workpiece, and can maintain the gloss of the magnesium alloy.
[0103] In some embodiments, the conversion solution may at least include organosiloxane, fluorosilicate, silica sol, ammonium metavanadate, and a solvent. The process of soaking or spraying the magnesium alloy workpiece with the conversion solution can be achieved through the following steps: Based on the organosiloxane, fluorosilicate, silica sol, and ammonium metavanadate in the conversion solution, a chemical reaction occurs with the magnesium alloy workpiece to generate a conversion film adsorbed with metavanadate on the surface of the magnesium alloy workpiece.
[0104] In some embodiments, the pH value of the conversion solution is between 6.0 and 6.5, showing weak acidity. First, an anodic reaction occurs on the surface of the magnesium alloy workpiece, and a small amount of magnesium ions (Mg 2+ ) dissolve out from the magnesium alloy workpiece and react with silicate ions (SiO 3 2- ) in the solution to form magnesium oxide (MgO) on the surface of the magnesium alloy workpiece. Silica sol and organosiloxane react with the oxides or hydroxyl groups on the surface of the magnesium alloy during the reaction, and through hydrolysis and condensation reactions, a uniform silica (SiO 2 ) film is formed, thereby generating a conversion film composed of a composite of magnesium oxide and silicon oxide.
[0105] In some embodiments, ammonium metavanadate is used to provide metavanadate (VO 3 2-) The vanadate is adsorbed on the oxide film that has already formed on the surface of the magnesium alloy. The vanadate ions can react with the treatment solution containing colored ions to form a compound with a specific color, which can endow the film layer with a specific color.
[0106] In some embodiments, before the surface treatment of the magnesium alloy workpiece, it is a polished magnesium alloy workpiece with a mirror effect. After the conversion film is formed by the surface treatment, the surface treatment will not overly dissolve the surface of the magnesium alloy, causing the mirror effect of the magnesium alloy workpiece to disappear. Therefore, in the embodiments of the present application, the difference between the refractive index of the magnesium alloy workpiece with the conversion film and the refractive index of the magnesium alloy workpiece is less than a preset threshold (for example, 30%), that is, the conversion film has a small impact on the refractive index of the magnesium alloy workpiece. That is to say, the magnesium alloy workpiece with the conversion film still has a mirror effect, reducing the problem that the appearance of electronic products has no metallic luster.
[0107] In the embodiments of the present application, the conversion solution uses a combination of silane and fluorosilicate to perform surface treatment on the magnesium alloy workpiece, with a relatively low impact on the surface of the magnesium alloy, maintaining the gloss and mirror effect of the surface of the magnesium alloy workpiece.
[0108] In some embodiments, step S302 can be implemented through step S3021:
[0109] Step S3021: Under the second process conditions, the magnesium alloy workpiece with the conversion film having an oxidizing substance adsorbed on its surface is soaked or sprayed with the treatment solution, so that the colored ions in the treatment solution react with the oxidizing substance to form a complex reaction, and a colored conversion film is formed on the surface of the conversion film; wherein, the pH value of the treatment solution is greater than the pH value of the conversion solution.
[0110] Here, the second process conditions may refer to soaking or spraying the magnesium alloy workpiece with the conversion film having an oxidizing substance adsorbed on its surface with the treatment solution at 20 - 30 °C for 90 - 180 s.
[0111] In some embodiments, the treatment solution may include a catalyst, a complexing agent, a colored ion compound, sodium gluconate, sodium citrate, and a solvent.
[0112] Here, the complexing agent may include disodium ethylenediaminetetraacetate (EDTA disodium salt). The complexing agent can react with metal ions to form stable complexes and can also prevent metal ions from participating in other chemical reactions, so that no other substances will appear in the colored conversion film.
[0113] In the embodiments of the present application, during the complexation reaction, the colored ions react with the oxidizing substances (such as vanadate or oxidation salts) attached to the surface of the conversion film to generate colored acid salts and oxides, presenting corresponding colors, that is, the colored conversion film.
[0114] The catalyst may include one of the following: potassium fluorozirconate and manganese sulfate, which are used to catalyze the reaction between a colored ionic compound and an oxidizing substance.
[0115] The colored ionic compound may at least include one of the following: iron ion complex (yellow), copper ion complex (blue), manganese ion complex (pink), and nickel ion complex (green).
[0116] Sodium gluconate and sodium citrate can be used to adjust the pH value of the treatment liquid so that the pH value of the treatment liquid is greater than the pH value of the conversion liquid. For example, the pH value of the treatment liquid can be between 10 and 11.
[0117] In some embodiments, the treatment liquid may include manganese sulfate, ferrous sulfate, disodium EDTA, sodium gluconate, sodium citrate, and a solvent. At this time, the content of manganese sulfate in the treatment liquid can be 10 - 15 g / L. Exemplarily, the content of manganese sulfate in the treatment liquid can be 10, 12, 15, or a value within the range composed of any two of these values. The content of ferrous sulfate in the treatment liquid can be 5 - 7 g / L. Exemplarily, the content of ferrous sulfate in the treatment liquid can be 5, 6, 7, or a value within the range composed of any two of these values. The content of disodium EDTA in the treatment liquid can be 8 - 10 g / L. Exemplarily, the content of manganese sulfate in the treatment liquid can be 8, 9, 10, or a value within the range composed of any two of these values. The content of sodium gluconate in the treatment liquid can be 5 - 10 g / L. Exemplarily, the content of sodium gluconate in the treatment liquid can be 5, 8, 10, or a value within the range composed of any two of these values. The content of sodium citrate in the treatment liquid can be 8 - 10 g / L. Exemplarily, the content of sodium citrate in the treatment liquid can be 8, 9, 10, or a value within the range composed of any two of these values.
[0118] In some embodiments, the treatment liquid may further include potassium hexafluorozirconate, disodium EDTA, sodium gluconate, sodium citrate, and a solvent. At this time, the content of potassium hexafluorozirconate in the treatment liquid may be 15-20 g / L. Exemplarily, the content of potassium hexafluorozirconate in the treatment liquid may be 15, 17, 19, or a value within the range composed of any two of these values. The content of disodium EDTA in the treatment liquid may be 5-8 g / L. Exemplarily, the content of manganese sulfate in the treatment liquid may be 5, 6, 7, or a value within the range composed of any two of these values. The content of sodium gluconate in the treatment liquid may be 5-10 g / L. Exemplarily, the content of sodium gluconate in the treatment liquid may be 5, 8, 10, or a value within the range composed of any two of these values. The content of sodium citrate in the treatment liquid may be 8-10 g / L. Exemplarily, the content of sodium citrate in the treatment liquid may be 8, 9, 10, or a value within the range composed of any two of these values.
[0119] In the embodiments of the present application, the treatment liquid can be adjusted according to the color of the colored conversion film, and the embodiments of the present application do not make any restrictions.
[0120] The surface treatment method, conversion liquid, and treatment liquid provided by the embodiments of the present application are not limited to the application of magnesium alloys and can be used for any metal that can react with the conversion liquid and treatment liquid to form a colored conversion film on the metal surface.
[0121] In the embodiments of the present application, a thin color layer composed of colored acid salts or non-ferrous metal oxides is formed through colored ions in the treatment liquid, and finally a highly transparent conversion film layer with a specified color is formed on the surface of the magnesium alloy workpiece, which can provide good adhesion and weather resistance for subsequent painting.
[0122] In the embodiments of the present application, γ-(2,3-epoxypropoxy)propyltrimethoxysilane with a content of 25 g / L, potassium fluorosilicate with a content of 9 g / L, silica sol with a content of 11 g / L, ammonium bifluoride with a content of 9 g / L, sodium citrate with a content of 7 g / L, ammonium metavanadate with a content of 2 g / L, and fatty alcohol polyoxyethylene ether with a content of 0.3 g / L are used as the conversion liquid. The pH value of the conversion liquid is 6.3. The magnesium alloy workpiece is immersed in the conversion liquid at 25 °C for 120 seconds and then taken out. After draining in the air for 30 seconds, the magnesium alloy workpiece is immersed in the treatment liquid for 120 seconds and then taken out. Among them, the treatment liquid uses potassium hexafluorozirconate with a content of 17 g / L, disodium EDTA with a content of 7 g / L, sodium gluconate with a content of 7.5 g / L, and sodium citrate with a content of 9 g / L. The pH value of the treatment liquid is 10.5. The magnesium alloy workpiece is immersed in the chemical liquid at 25 °C for 120 seconds and then taken out. After drying at 150 °C, a transparent light blue film layer exists on the surface of the magnesium alloy workpiece, and after a 48-hour salt spray test, the film layer is not damaged. Figure 4It is a schematic diagram of a magnesium alloy workpiece with a light cyan film layer provided by an embodiment of the present application. As shown in the figure, the side wall 401 of the electronic device can obtain a light cyan film layer through the conversion liquid, treatment liquid, and surface treatment method provided by the embodiment of the present application, and maintain the metallic luster of the magnesium alloy workpiece, indicating that the components of the conversion liquid and treatment liquid of the present application are effective.
[0123] In the embodiment of the present application, γ-(2,3-epoxypropoxy)propyltrimethoxysilane with a content of 25 g / L, potassium fluorosilicate with a content of 9 g / L, silica sol with a content of 11 g / L, ammonium bifluoride with a content of 9 g / L, sodium citrate with a content of 7 g / L, ammonium metavanadate with a content of 2 g / L, and fatty alcohol polyoxyethylene ether with a content of 0.3 g / L are used as the conversion liquid. The pH value of the conversion liquid is 6.3. The magnesium alloy workpiece is immersed in the conversion liquid at 25 °C for 120 seconds and then taken out. After draining in the air for 30 seconds, the magnesium alloy workpiece is immersed in the treatment liquid for 120 seconds and then taken out. Among them, the treatment liquid uses manganese sulfate with a content of 12 g / L, ferrous sulfate with a content of 6 g / L, disodium EDTA with a content of 9 g / L, sodium gluconate with a content of 7.5 g / L, and sodium citrate with a content of 9 g / L. The pH value of the treatment liquid is 10.5. The magnesium alloy workpiece is immersed in the chemical liquid at 25 °C for 120 seconds and then taken out. After drying at 150 °C, a transparent light yellow film layer exists on the surface of the magnesium alloy workpiece, and after a 48-hour salt spray test, the film layer is not damaged. Figure 5 It is a schematic diagram of a magnesium alloy workpiece with a light yellow film layer provided by an embodiment of the present application. As shown in the figure, the side wall 501 of the electronic device can obtain a light yellow protective film layer through the conversion liquid, treatment liquid, and surface treatment method provided by the embodiment of the present application, and maintain the metallic luster of the magnesium alloy workpiece, indicating that the components of the conversion liquid and treatment liquid of the present application are effective.
[0124] In some embodiments, before the surface treatment of the magnesium alloy workpiece, the magnesium alloy workpiece is also polished, dewaxed, degreased, etc. Therefore, the surface treatment method provided by the embodiment of the present application further includes step S1 and step S2:
[0125] Step S1: Obtain a magnesium alloy workpiece with a mirror effect after high-brightness polishing treatment.
[0126] Here, the high-brightness polishing can be any feasible polishing method such as mechanical polishing, electrolytic polishing, chemical polishing, chemical mechanical polishing, etc., so that the magnesium alloy workpiece has a mirror effect.
[0127] Step S2: Clean the magnesium alloy workpiece with the mirror effect to obtain the magnesium alloy workpiece; the cleaning includes at least dewaxing cleaning and degreasing cleaning.
[0128] Here, cleaning may refer to putting the magnesium alloy after bright polishing treatment into a dewaxing agent for dewaxing cleaning, and then putting the magnesium alloy workpiece after dewaxing cleaning into a degreasing agent for degreasing cleaning to obtain a magnesium alloy workpiece for surface treatment. Here, the types of the dewaxing agent and the degreasing agent are not limited.
[0129] In some embodiments, after the surface treatment of the magnesium alloy workpiece, subsequent cleaning of the magnesium alloy workpiece is also required. Therefore, the surface treatment method further includes step S21 and step S22:
[0130] Step S21: Wash the magnesium alloy workpiece with the colored conversion film to obtain a washed magnesium alloy workpiece.
[0131] In the embodiments of the present application, water washing is to remove residual chemical substances to avoid adverse effects on subsequent processes (such as electroplating, painting, etc.). Here, water washing can be to put the workpiece into flowing deionized water for preliminary rinsing to remove most of the residual liquid on the surface, and then soak the workpiece in deionized water, shake the workpiece or use an ultrasonic cleaning device to further remove the surface residues to obtain a washed magnesium alloy workpiece.
[0132] Step S22: Dry the washed magnesium alloy workpiece to obtain a dried magnesium alloy workpiece.
[0133] In some embodiments, the drying treatment can be to put the washed magnesium alloy workpiece into a drying furnace for drying treatment until it is completely dry. Here, the drying temperature can be set at 40 - 50 °C, and the drying duration is 5 - 10 minutes, which can ensure uniform drying of the workpiece surface and enhance the stability of the conversion film.
[0134] The embodiments of the present application further provide a magnesium alloy workpiece, on the surface of which a colored conversion film is formed; the colored conversion film is formed by using a conversion liquid to perform surface treatment on the surface of the magnesium alloy workpiece to form a conversion film with an oxidizing substance adsorbed on the surface of the magnesium alloy workpiece; and is formed on the surface of the conversion film based on the reaction of a treatment liquid with colored ions and the oxidizing substance adsorbed on the surface of the conversion film; wherein, the pH value of the conversion liquid is between 6.0 and 6.5.
[0135] Here, the magnesium alloy workpiece with a colored conversion film can be widely applied in multiple fields, especially in scenarios where corrosion resistance, decoration, and specific functions need to be considered. For example, for the outer shells of electronic products such as laptops and mobile phones, a protective film with various colors such as golden yellow, yellow, and rainbow color can be formed on the magnesium alloy surface. These film layers not only have good corrosion resistance but also can meet specific decoration requirements. It can also be applied to different application scenarios such as the aerospace field, the automotive industry, and medical devices.
[0136] Another embodiment of the present application provides an electronic device, which includes a magnesium alloy workpiece with a colored conversion film formed on its surface; the colored conversion film is formed by using a conversion solution to perform surface treatment on the surface of the magnesium alloy workpiece, and a conversion film with an oxidizing substance adsorbed on its surface is formed on the surface of the magnesium alloy workpiece; based on a treatment solution with colored ions, it reacts with the oxidizing substance adsorbed on the surface of the conversion film to form on the surface of the conversion film; wherein, the pH value of the conversion solution is between 6.0 and 6.5.
[0137] In some embodiments, the magnesium alloy workpiece with a colored conversion film can be the housing of an electronic device, which can not only enhance the appearance diversity of the electronic device, but also enhance the protection performance and endow a specific color to meet aesthetic requirements. The electronic device can be a laptop, a mobile phone, a smart wearable device, etc.
[0138] Another embodiment of the present application provides a preparation method, including: obtaining a die-cast magnesium alloy workpiece; performing surface treatment on a preset position of the magnesium alloy workpiece to form a colored conversion film on the surface of the preset position; wherein, the surface treatment includes using a conversion solution to perform surface treatment on the surface of the magnesium alloy workpiece to form a conversion film with an oxidizing substance adsorbed on its surface; based on a treatment solution with colored ions, it reacts with the oxidizing substance adsorbed on the surface of the conversion film to form a colored conversion film on the surface of the conversion film; wherein, the pH value of the conversion solution is between 6.0 and 6.5.
[0139] In the embodiments of the present application, based on the use of the magnesium alloy workpiece, the magnesium alloy workpiece can be die-cast, such as for automotive parts, laptop housings, mobile phone housings, etc.
[0140] After obtaining the die-cast magnesium alloy workpiece, determine the preset position on the magnesium alloy workpiece that needs to be surface-treated, and perform surface treatment on the preset position to form a colored conversion film that completely covers the surface of the preset position. Here, the preset position refers to any position on the magnesium alloy workpiece set by a technician, such as the entire outer surface of the magnesium alloy workpiece, or the side wall of the magnesium alloy, etc.
[0141] Figure 6 is a schematic structural diagram of the die-cast magnesium alloy workpiece provided by the embodiment of the present application, as Figure 6As shown, after the magnesium alloy workpiece is die-cast and formed, it can be used as a laptop shell. The outer surface 601 of the laptop shell can be a preset position that needs to be surface-treated as set by technicians. A conversion liquid can be used to perform surface treatment on the outer surface 601, and a conversion film with an oxidizing substance adsorbed on its surface is formed on the outer surface 601; based on a treatment liquid with colored ions, a reaction is carried out with the oxidizing substance adsorbed on the surface of the conversion film, and a colored conversion film is formed on the surface of the conversion film to achieve colored treatment of the outer surface 601.
[0142] In some embodiments, it can also be that the side wall 602 of the laptop shell is the preset position, and a colored conversion film is generated on the side wall 602 to achieve colored treatment of the side wall 602.
[0143] Next, an exemplary application of the embodiments of the present application in an actual application scenario will be described.
[0144] In order to form a transparent film layer with a certain color on the magnesium alloy workpiece in the embodiments of the present application, the formation of the colored layer on the surface of the first colorless film layer is achieved through a two-step method. In the implementation of the first film layer, a combination of silane and fluorosilicate is used, which can not only form a transparent protective film but also minimize the impact on the magnesium alloy surface. Then, after the formation of the first film layer, the surface is activated to adsorb an oxidant to oxidize and form a film on the metal ions, so that the protective film forms a specified color change.
[0145] Figure 7 is a schematic flow chart of forming a colored film on the magnesium alloy surface provided by the embodiments of the present application. As Figure 7 shown, the colored film can be achieved through steps S701 to S706:
[0146] Step S701: Put the magnesium alloy treated by high-brightness polishing into a dewaxing agent for treatment to obtain a dewaxed magnesium alloy workpiece.
[0147] Step S702: Put the dewaxed magnesium alloy workpiece into a degreasing agent for treatment to obtain a degreased magnesium alloy workpiece.
[0148] Step S703: Immerse the degreased magnesium alloy workpiece in a first chemical treatment liquid to obtain a magnesium alloy workpiece with a transparent film.
[0149] In the embodiments of the present application, the first chemical treatment liquid may include γ-(2,3-epoxypropoxy)propyltrimethoxysilane with a content of 18 - 32 g / L, potassium fluorosilicate with a content of 8 - 10 g / L, silica sol with a content of 10 - 12 g / L, ammonium bifluoride with a content of 8 - 10 g / L, sodium citrate with a content of 5 - 8 g / L, ammonium metavanadate with a content of 1 - 3 g / L, and AEO-7 (i.e., fatty alcohol polyoxyethylene ether) with a content of 0.25 - 0.4 g / L, an acid regulator, a base regulator, and a solvent.
[0150] In some embodiments, the pH value of the first chemical treatment solution is between 6.0 and 6.5.
[0151] In the embodiments of the present application, at 20-30 °C, the degreased magnesium alloy workpiece is immersed in the first chemical treatment solution for 60-180 s. Through the reaction of fluorosilicate, silica sol and organosiloxane with the surface layer of the magnesium alloy, a transparent film composed of magnesium oxide and silicon oxide is formed, and oxidizing substances such as metavanadate are adsorbed on the surface of the transparent film.
[0152] Step S704: Immerse the magnesium alloy workpiece with the transparent film in the second chemical treatment solution to obtain a magnesium alloy workpiece with a colored film.
[0153] In some embodiments, in order to make the surface of the magnesium alloy workpiece show a light yellow color, a second chemical treatment solution containing ferrous ions can be used to react with the oxidizing substances on the surface of the magnesium alloy workpiece to form a colored film. Here, the second chemical treatment solution can include manganese sulfate with a content of 10-15 g / L, ferrous sulfate with a content of 5-7 g / L, disodium EDTA with a content of 8-10 g / L, sodium gluconate with a content of 5-10 g / L, and sodium citrate with a content of 8-10 g / L.
[0154] In some embodiments, the pH value of the second chemical treatment solution is between 10 and 11.
[0155] In the embodiments of the present application, at 20-30 °C, the magnesium alloy workpiece with the transparent film is immersed in the second chemical treatment solution for 80-180 s. Thin salts or metal oxides are formed by the metal colored ions in the second chemical treatment solution to form a color layer, and finally a highly transparent conversion film layer with a certain color, that is, a colored film, is formed on the bright surface of the magnesium alloy.
[0156] Step S705: Wash the magnesium alloy workpiece with the colored film thoroughly to obtain a washed magnesium alloy workpiece.
[0157] Step S706: Dry the washed magnesium alloy workpiece to obtain a magnesium alloy workpiece with a color.
[0158] In the embodiments of the present application, the magnesium alloy workpiece with the colored film can be washed and dried thoroughly, and finally a magnesium alloy workpiece with a light yellow film is obtained.
[0159] Through the film-forming method provided by the embodiments of the present application, a uniform highly transparent colored surface film layer can be generated on the surface of the magnesium alloy, which can provide good adhesion and weather resistance for subsequent painting.
[0160] Comparative Example 1
[0161] Using γ-(2,3-epoxypropoxy)propyltrimethoxysilane with a content of 25 g / L, potassium fluorosilicate with a content of 9 g / L, silica sol with a content of 11 g / L, ammonium bifluoride with a content of 9 g / L, sodium citrate with a content of 7 g / L, ammonium metavanadate with a content of 2 g / L, and fatty alcohol polyoxyethylene ether with a content of 0.3 g / L as the chemical solution, the pH value of the chemical solution is 6.3. The magnesium alloy workpiece is immersed in the conversion solution at 25 °C for 120 seconds and then taken out. After drying at 150 °C, there is no colored film on the surface of the magnesium alloy workpiece.
[0162] Comparative Example 2
[0163] Using potassium fluorozirconate with a content of 17 g / L, disodium EDTA with a content of 7 g / L, sodium gluconate with a content of 7.5 g / L, and sodium citrate with a content of 9 g / L as the chemical solution, the pH value of the chemical solution is 10.5. The magnesium alloy workpiece is immersed in the chemical solution at 25 °C for 120 seconds and then taken out. After drying at 150 °C, there is no film layer on the surface of the magnesium alloy workpiece.
[0164] Comparative Example 3
[0165] Using manganese sulfate with a content of 12 g / L, ferrous sulfate with a content of 6 g / L, disodium EDTA with a content of 9 g / L, sodium gluconate with a content of 7.5 g / L, and sodium citrate with a content of 9 g / L as the chemical solution, the pH value of the chemical solution is 10.5. The magnesium alloy workpiece is immersed in the chemical solution at 25 °C for 120 seconds and then taken out. After drying at 150 °C, there is no film layer on the surface of the magnesium alloy workpiece.
[0166] Comparative Example 4
[0167] Using γ-(2,3-epoxypropoxy)propyltrimethoxysilane with a content of 25 g / L, potassium fluorosilicate with a content of 9 g / L, silica sol with a content of 11 g / L, ammonium bifluoride with a content of 9 g / L, sodium citrate with a content of 7 g / L, ammonium metavanadate with a content of 2 g / L, and fatty alcohol polyoxyethylene ether with a content of 0.3 g / L as the conversion solution, the pH value of the conversion solution is 6.3. The magnesium alloy workpiece is immersed in the conversion solution at 25 °C for 120 seconds and then taken out. After draining in the air for 30 seconds, the magnesium alloy workpiece is immersed in the treatment solution for 120 seconds and then taken out. Among them, the treatment solution uses potassium fluorozirconate with a content of 0 g / L, disodium EDTA with a content of 7 g / L, sodium gluconate with a content of 7.5 g / L, and sodium citrate with a content of 9 g / L. The pH value of the treatment solution is 10.5. The magnesium alloy workpiece is immersed in the chemical solution at 25 °C for 120 seconds and then taken out. After drying at 150 °C, after 36 hours of neutral salt spray test, the surface of the magnesium alloy workpiece is a colorless film layer, and there is no transparent light blue film layer.
[0168] Compared with Comparative Examples 1 to 4, the conversion solution and the surface treatment method provided by the embodiments of the present application can form a colored film layer on the surface of the magnesium alloy.
[0169] The above is only the embodiment of the present application and is not intended to limit the protection scope of the present application. Any modification, equivalent replacement, and improvement made within the spirit and scope of the present application are included in the protection scope of the present application.
[0170] It should be understood that the term "one embodiment" or "an embodiment" mentioned throughout the specification means that a specific feature, structure, or characteristic related to the embodiment is included in at least one embodiment of the present application. Therefore, the appearances of the phrase "in one embodiment" or "in an embodiment" throughout the specification do not necessarily refer to the same embodiment. In addition, these specific features, structures, or characteristics can be combined in any suitable manner in one or more embodiments. It should be understood that in various embodiments of the present application, the sequence numbers of the above processes do not mean the order of execution. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation to the implementation process of the embodiments of the present application. The sequence numbers of the embodiments of the present application are only for description and do not represent the advantages or disadvantages of the embodiments.
[0171] It should be noted that in this text, the term "comprising", "including" or any other variation thereof is intended to cover a non-exclusive inclusion, such that a process, method, or device comprising a series of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such process, method, or device. Without further limitation, an element defined by the phrase "comprising a..." does not exclude the presence of additional identical elements in the process, method, article, or device comprising that element. In several embodiments provided by the present application, it should be understood that the disclosed devices and methods can be implemented in other ways. The device embodiments described above are merely illustrative. For example, the division of the units is only a logical functional division, and there can be other division methods in actual implementation, such as: multiple units or components can be combined, or can be integrated into another system, or some features can be ignored, or not executed.
[0172] The above is only the implementation manner of the present application, but the protection scope of the present application is not limited thereto. Any person skilled in the art can easily think of changes or replacements within the technical scope disclosed by the present application, and all should be covered by the protection scope of the present application. Therefore, the protection scope of the present application should be subject to the protection scope of the claims.
Claims
1. A conversion solution, comprising at least organic siloxane, fluorosilicate, silica sol, ammonium metavanadate and a solvent. The conversion liquid according to claim 1 , which is used for surface treatment of metal structures.
3. The conversion solution according to claim 1, wherein the content of the organosiloxane in the conversion solution is 18 to 32 g / L; The content of the fluorosilicate in the conversion liquid is 8 to 10 g / L; The content of the silica sol in the conversion liquid is 10-12 g / L; The content of the ammonium metavanadate in the conversion solution is 1-3 g / L.
4. The conversion solution according to claim 3, wherein the organosiloxane comprises γ-(2,3-epoxypropoxy)propyltrimethoxysilane; the fluorosilicate comprises potassium fluorosilicate; and the solvent comprises deionized water; The conversion liquid also includes ammonium bifluoride, sodium citrate, fatty alcohol polyoxyethylene ether, an acidic regulator and an alkaline regulator. The acidic regulator includes citric acid or hydrofluoric acid, and the alkaline regulator includes ammonia water or sodium hydroxide. The pH value of the conversion liquid is between 6.0 and 6.
5.
5. The conversion solution according to claim 4, wherein the content of ammonium bifluoride in the conversion solution is 8-10 g / L; The content of sodium citrate in the conversion solution is 5-8 g / L; The content of the fatty alcohol polyoxyethylene ether in the conversion liquid is 0.25-0.4 g / L.
6. A surface treatment method, comprising: The surface of the magnesium alloy workpiece is treated with a conversion liquid to form a conversion film on the surface of the magnesium alloy workpiece with oxidizing substances adsorbed on the surface; wherein the pH value of the conversion liquid is between 6.0 and 6.5; The treatment liquid containing colored ions reacts with the oxidizing substances adsorbed on the surface of the conversion film to form a colored conversion film on the surface of the conversion film.
7. The surface treatment method according to claim 6, wherein the surface treatment is performed on the surface of the magnesium alloy workpiece using a conversion liquid to form a conversion film on the surface of the magnesium alloy workpiece with oxidizing substances adsorbed on the surface, comprising: Under the first process condition, the magnesium alloy workpiece is immersed or sprayed with the conversion liquid to form a conversion film having oxidizing substances adsorbed on the surface of the magnesium alloy workpiece; Wherein, the transparency of the conversion film is greater than a preset transparency threshold.
8. The surface treatment method according to claim 7, wherein the conversion solution comprises at least organosiloxane, fluorosilicate, silica sol and ammonium metavanadate; The step of using the conversion liquid to immerse or spray the magnesium alloy workpiece to form a conversion film having oxidizing substances adsorbed on the surface of the magnesium alloy workpiece comprises: Based on the organic siloxane, fluorosilicate, silica sol and ammonium metavanadate in the conversion liquid, a chemical reaction occurs with the magnesium alloy workpiece to form a conversion film adsorbed with metavanadate on the surface of the magnesium alloy workpiece; Wherein, the difference between the refractive index of the magnesium alloy workpiece having the conversion film and the refractive index of the magnesium alloy workpiece is less than a preset threshold, and the conversion film is a protective film composite of magnesium oxide and silicon oxide.
9. The surface treatment method according to any one of claims 6 to 8, wherein the treatment liquid containing colored ions reacts with the oxidizing substances adsorbed on the surface of the conversion film to form a colored conversion film on the surface of the conversion film, comprising: Under the second process condition, the magnesium alloy workpiece having the conversion film on the surface of which the oxidizing substance is adsorbed is immersed or sprayed with the treatment liquid, so that the colored ions in the treatment liquid react with the oxidizing substance to form the colored conversion film on the surface of the conversion film; Wherein, the pH value of the treatment liquid is greater than the pH value of the conversion liquid, and the treatment liquid comprises: a catalyst, a complexing agent, a colored ion compound, sodium gluconate, sodium citrate and a solvent; The solvent includes deionized water; the complexing agent includes disodium ethylenediaminetetraacetic acid; the catalyst includes one of the following: potassium fluorozirconate and manganese sulfate; the colored ion compound includes at least one of the following: an iron ion complex, a copper ion complex, a manganese ion complex and a nickel ion complex.
10. An electronic device, comprising a magnesium alloy workpiece, wherein a colored conversion film is formed on a surface of the magnesium alloy workpiece; The colored conversion film is formed by using a conversion liquid to treat the surface of the magnesium alloy workpiece, and the conversion film with oxidizing substances adsorbed on the surface of the magnesium alloy workpiece is formed on the surface of the magnesium alloy workpiece; the treatment liquid with colored ions reacts with the oxidizing substances adsorbed on the surface of the conversion film, and the conversion film is formed on the surface of the conversion film; wherein, The pH value of the conversion solution is between 6.0 and 6.
5.
11. A preparation method, comprising: Obtaining a die-cast magnesium alloy workpiece; Performing surface treatment on a preset position of the magnesium alloy workpiece to form a colored conversion film on the surface of the preset position; The surface treatment comprises: using a conversion liquid to perform surface treatment on the surface of the magnesium alloy workpiece, thereby forming a conversion film on the surface of the magnesium alloy workpiece with oxidizing substances adsorbed on the surface; using a treatment liquid having colored ions to react with the oxidizing substances adsorbed on the surface of the conversion film, thereby forming a colored conversion film on the surface of the conversion film; wherein the pH value of the conversion liquid is between 6.0 and 6.5.